Exploring EFL Graduate Students' Perspectives and Strategies to Improve English Speaking Skills - Jeane Theresia Limeranto; Barly Bram (Faculty of Language and Literature, University of Surakarta, 2022)
Even though Indonesian EFL learners have been studying English since elementary school, many may still consider speaking one of the most challenging language skills. Consequently, when they move to the advanced level, they are required to master more complex speaking skills. Indonesian EFL graduate students faced some problems during learning that can contribute to their speaking performance. Therefore, it is urgent for this study to investigate EFL graduate students’ perspectives on their speaking challenges and strategies used to improve their speaking skills. This study used a qualitative method and a semi-structured interview to obtain deep insight into participants’ perspectives. The participants were EFL graduate students who are taking an English Education Master’s Program. Results showed that some factors influenced their speaking skills in an academic context, such as a lack of accurate pronunciation and lack of vocabulary knowledge and that they used effective speaking strategies for improving their ability in speaking. It is expected that the findings would assist EFL graduate students in uncovering their speaking challenges so that they could perform better when using their spoken English.